2020
DOI: 10.1055/s-0040-1717000
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Effectiveness of e-Learning Classes during COVID-19 Pandemic: A Nation-Wide Survey of Pakistani Undergraduate Dentistry Students

Abstract: Objectives The main aim of this study was to determine the undergraduate dental students’ self-reported effectiveness of online classes offered by various dental institutes of Pakistan. Materials and Methods A cross-sectional study was conducted using an online survey. A pretested and validated questionnaire comprising of 31 questions was circulated among dental students. The study participants were inquired about the perceived level of accessibility of resources and the effectiveness of online teaching. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 27 publications
12
106
1
2
Order By: Relevance
“…In line with it, Sarwar et al (2020) conducted a study on 1207 dental students that also described educational level as an important predictor of satisfaction. They revealed that first-year students were not satisfied with this mode of learning that might be due to poor interaction with teachers [52].…”
Section: Discussionmentioning
confidence: 99%
“…In line with it, Sarwar et al (2020) conducted a study on 1207 dental students that also described educational level as an important predictor of satisfaction. They revealed that first-year students were not satisfied with this mode of learning that might be due to poor interaction with teachers [52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Prieto et al identified that dental students described teachers as showing good predisposition, flexibility, availability, and empathy through the course but also suggested better staff training in online learning [ 14 ]. A study conducted by Sarwar et al [ 17 ] among dentistry undergraduate students from medical universities in Pakistan showed that the majority of respondents were dissatisfied with the institutional learning management system, the level of teachers’ training for online lectures, and the quality of the available learning resources. The authors identified that the worst rating was reported for items inquiring about the effectiveness of online classes; freshmen reported the poorest interaction with teachers and a strong disagreement with the effectiveness of online classes.…”
Section: Discussionmentioning
confidence: 99%
“…In light of national COVID-19 infection-control recommendations, dental faculties had to suspend in-person instruction, and teaching activity was conducted online. Some researchers who focused on online dental education pointed out the rapid change adopted by dental faculties in many countries, such as the USA [ 6 , 7 , 8 , 9 ], Germany [ 10 ], Italy [ 11 ], China [ 12 , 13 ], Chile [ 14 ], Brazil [ 8 , 15 , 16 ], Pakistan [ 17 ], Nepal [ 18 , 19 ], Indonesia [ 20 ], India [ 21 , 22 ], Jordan [ 23 ], Romania [ 24 , 25 , 26 ], Portugal [ 27 , 28 ], Cyprus [ 29 ], Australia [ 8 , 30 ], and Spain [ 31 ]. During the first year of the pandemic, the academic research teams additionally wanted to identify the differences between countries in what aspects of dental education were disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expansion of digital education has produced dissatisfaction with learning due to poor internet connection, methods of presentation, and level of participation in class activities. This could ultimately lead to a decrease in adolescent knowledge of health conditions [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the expansion of digital education has produced dissatisfaction with learning due to poor internet connection, methods of presentation, and level of participation in class activities. This could ultimately lead to a decrease in adolescent knowledge of health conditions [ 35 ]. The appropriate use of health services to promote sexual health should encompass the normal and abnormal changes that may present alongside sexual development.…”
Section: Reviewmentioning
confidence: 99%